New spaces of development partnership: Rethinking international volunteering. (October 2015) - Schech, Susanne; Mundkur, Anuradha; Skelton, Tracey; Kothari, Uma
The concept of partnership is frequently invoked in international development as discourse and policy prescription to better understand relationships and engagements between donors and beneficiaries. Despite the increasing prominence of the idea of partnerships, in reality mutual, equal and sustainable development partnerships remain limited. This article examines the extent to which recent growth in international development volunteering can provide new spaces where equitable and sustainable partnerships may emerge. This review highlights partnership's legacy in discourses of participation and explores the changing role and impact of development volunteering. We identify three spaces where new kinds of alliances and relationships can be forged – personal learning, policy and geopolitical.